2016
DOI: 10.1002/mrm.26231
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation properties of human umbilical cord blood at 1.5 Tesla

Abstract: Purpose-To characterize the MRI relaxation properties of human umbilical cord blood at 1.5 Tesla.Methods-Relaxometry measurements were performed on cord blood specimens (N=88, derived from 6 caesarean deliveries) spanning a broad range of hematocrits (Hct=0.19-0.76) and oxygen saturations (sO 2 =4-100%), to characterize the dependence of T 1 and T 2 on these blood properties.Adult blood data (N = 31 specimens, derived from two volunteers) were similarly studied to validate our experimental methods by compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 33 publications
10
91
0
Order By: Relevance
“…Recognizing that these differences would likely affect MRI relaxation properties, the relationships between fetal blood relaxation times and oxygen saturation and hematocrit at 1.5T and 3T have been characterized by using umbilical cord blood samples harvested from human cesarean deliveries. This approach confirmed the reliability of this method for calculating blood hematocrit and oxygen saturation from measurements of the T 1 and T 2 relaxation times of fetal blood …”
Section: Magnetic Resonance Oximetrysupporting
confidence: 83%
See 1 more Smart Citation
“…Recognizing that these differences would likely affect MRI relaxation properties, the relationships between fetal blood relaxation times and oxygen saturation and hematocrit at 1.5T and 3T have been characterized by using umbilical cord blood samples harvested from human cesarean deliveries. This approach confirmed the reliability of this method for calculating blood hematocrit and oxygen saturation from measurements of the T 1 and T 2 relaxation times of fetal blood …”
Section: Magnetic Resonance Oximetrysupporting
confidence: 83%
“…This approach confirmed the reliability of this method for calculating blood hematocrit and oxygen saturation from measurements of the T 1 and T 2 relaxation times of fetal blood. 58,63,64…”
Section: Magnetic Resonance Oximetrymentioning
confidence: 99%
“…As the field strength is decreased, the relative contribution of chemical exchange to relaxation is expected to increase, as its contribution changes at a less than quadratic rate with respect to B 0 , whereas the diffusion contribution is expected to change at a quadratic rate . That the results of the Luz‐Meiboom exchange model fits gave an exchange time of 2.2 ms, whereas the exchange lifetime of water in RBCs is generally considered to be approximately 10 ms , is evidence that the LM chemical exchange model alone is insufficient to describe transverse relaxation at 3 T. This finding of lower than expected τ ex is consistent with several earlier studies with B 0 of approximately 1.5 to 4.7 T . Invariably, both relaxation mechanisms contribute to T 2 decay, and to what extent is a complex issue that further underscores the limitations of describing the relaxation by a single mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…Parameter values used in this study, along with those reported in previous work , were obtained from (and therefore apply to) measurements acquired at 37 °C. Normal variation in body temperature is small (36.5 °C–37.5 °C); however, fever can elevate temperatures to ∼40 °C.…”
Section: Discussionmentioning
confidence: 99%